An application of range-frequency striations to seafloor inversion in shallow oceans - Jones, Adrian; Bartel, D.; Clarke, P. (na, 2012)
For shallow oceans, as is well known, multi-path interference generates a pattern of striations when broadband data received from a source are viewed on a range-frequency display. The frequency variations within this data are known to be related to the ocean depth, and to the seafloor acoustic properties (Jones and Clarke, Proceedings of 20th Intl. Congress on Acoustics, ICA 2010). Using a process in which the frequency spacing of the data is extracted, it is shown that a reasonable description of the seafloor acoustic properties may be inverted from the striations. The technique is demonstrated by simulations for a seafloor consisting of a uniform half-space.